(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: This study aims to evaluate the factors affecting the outcomes of dual-task cognitive-motor intervention on a treadmill in patients with Parkinson’s disease. Subjects and methods: The study included 33 patients with Parkinson’s disease at the National Geriatric Hospital from January 2024 to September 2024. This was a non-controlled interventional study. Patients in the study group were examined and assessed, then guided to participate in a dual-task intervention program on a treadmill at the hospital under the supervision of doctors and technicians to ensure adherence to the training program. Results: After the intervention, walking speed improved from 0.873 m/s to 0.903 m/s, and the 6-minute walking distance increased by an average of 25.83 ± 20.61 meters (p < 0.001). Significant improvements in motor function were notably higher in the following groups: those with a disease duration of 3 years or more (increased walking speed and reduced TUG time, p < 0.05); those with mild to moderate motor impairment (UPDRS III) (increased FGA scores, p = 0.032); those in early Hoehn and Yahr stages 1-2 (increased 6-minute walking distance, p = 0.017). The improvement in gait (FGA) showed a strong positive correlation with overall motor recovery (r = 0.81). Conclution: Positive improvements were observed in patients with a disease duration of more than 3 years, lower Hoehn and Yahr stages, and mild to moderate motor impairment as measured by UPDRS III.